(In)effectiveness of quality management systems and models of excellence in practice - Škafar, Branko (Array, 2019)
This paper presents some tools, used to ensure quality and excellence in organizations. On the way to ensure quality and excellence, which enable efficiency and effectiveness, organizations are assisted by well-known tools, with their common features being discussed. Based on the research, findings on the (non)functioning of these tools are given, with the focus on popular tools, such as ISO 9001, the EFQM model, etc. Results of the survey are used to suggest how to make the quality and excellence tools more useful and direct their usage toward realization of organizational effectiveness.